The Evaluation calendar of training young players volleyball in accordance with certain Biology indicators (Journal of the College of Basic Education, 2022)
The study aimed to identify The Evaluation calendar youth volleyball players training in accordance with certain Biology indicators (maximum consumption of oxygen, the oxygen peak during the effort, the number of times breathing during the effort, the average number of HEARTBEATS During Voltage), and aggressively pursued studies researcher descriptive approach to the Ever-growing manner on a sample of some of the clubs players Baghdad Volleyball (police, industry, and sea) in the sports season (2016-2017) (38) players were selected for the research sample of them by (100%) INTENTIONAL manner, after determining the search variables measured application of physical voltage test device (Fitmatepro System), three measurements of each indicator under discussion between each measurement and another one month for two months, and was dealing with the system (SPSS v24) for each of the values of the percentage of the mathematical community, delinquency The standard, Test (Levine) Homorganic discrepancy, testing and analysis of unilateral variation of repeated measurements (F) (Orthogonal) per sample Comparisons and testing,Sidak) Comparison between repeated circles associated with the sample, the researcher concluded that the training curriculum followed by coaches of young players volleyball made no progress in two indicators maximum oxygen consumption (VO2max, the average number of HEARTBEATS during effort (HR-Bpm), made clear in both the height of oxygen during effort (FeO2) rate and the number of times breathing during effort (RF) to young players volleyball.